2009
DOI: 10.1002/ptr.2882
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and antiinflammatory activities of grandisin extracted from Virola surinamensis

Abstract: The antinociceptive and antiinflammatory properties of the neolignan, grandisin, isolated from Virola surinamensis (Myristicaceae) were investigated. Grandisin (GRA) is present in several plant species from Brazil used in popular medicine for the treatment of disorders such as colic, inflammation, rheumatism, dyspepsia and liver dysfunction. These studies demonstrated that GRA is able to inhibit the acetic acid-induced writhing in mice dose-dependently, and that this effect is not caused by motor incoordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 21 publications
2
29
0
2
Order By: Relevance
“…(modified by Carvalho [8]). The number of writhes produced in each group for the following 30 min was counted and the results were expressed as mean ± standard error of mean (SEM) J Nat Med (2012) 66: 202-207 203 in percentage of control group.…”
Section: Acetic Acid-induced Abdominal Writhing Testmentioning
confidence: 99%
See 1 more Smart Citation
“…(modified by Carvalho [8]). The number of writhes produced in each group for the following 30 min was counted and the results were expressed as mean ± standard error of mean (SEM) J Nat Med (2012) 66: 202-207 203 in percentage of control group.…”
Section: Acetic Acid-induced Abdominal Writhing Testmentioning
confidence: 99%
“…The same volume of acetone was applied to the left ear. Four hours after the treatment with the solution of croton oil, the mice were killed by cervical dislocation and a plug (6 mm in diameter) was taken from both ears with a punch (modified by Carvalho [8]). The inflammatory response (edema) was monitored by measuring the differences in weight (mg) between the two plugs (D).…”
Section: Croton Oil-induced Ear Edema Testmentioning
confidence: 99%
“…The reduction in chemotaxis is an important response observed in treatments using anti-inflammatory drugs (Carvalho et al, 2009). It is known that vascular permeability is related to cell migration, therefore, we evaluated the capillary permeability by Evan's blue method (Mendonc¸a & Coutinho-Nett, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The residue purified by column chromatography on silica gel using hexane/ethyl acetate 8:2 as eluent. General procedure for the preparation of triazole derivatives (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) To a solution of terminal acetylenes 25a-d (2 mmol, 1.0 equiv) and azides 27a-d (2 mmol, 1.0 equiv) in dichloromethane (2 mL) and water (2 mL), were added CuSO 4 .5H 2 O pentahydrate (0.128 mmol, 0.064 equiv) and sodium ascorbate (0.352 mmol, 0.176 equiv). The reaction mixture was stirred for 24 h. Then was added a saturated solution of NH 4 Cl (30 mL) and the product was extracted with dichloromethane (3 × 20 mL).…”
Section: General Remarksmentioning
confidence: 99%
“…10,12,13 Among natural products, our research group has focused on the tetrahydrofuran neolignans, a class that exhibits a great number of biological activities including antibacterial, antifungal, antitumor, and anti-inflammatory. [14][15][16][17][18][19][20][21][22][23] The neolignans veraguensin 1, grandisin 2, and machilin G 3 ( Figure 1) have shown antitrypanosomal and antileishmanial activities. [14][15][16][17][18][19][20][21][22][23] Studies on the antitrypanosomal activity of compounds 1-3 found maximum inhibitory concentration (IC 50 ) values of 2.3, 3.7 and 2.2 µM, respectively.…”
Section: Introductionmentioning
confidence: 99%